Analisis Hukum Atas Akta Pendirian Koperasi Dimana Penandatanganan Akta Pendirian Didasarkan Kepada Surat Kuasa Di Bawah Tangan - Edwin Edwin; Ahmad Fauzi; Suprayitno Suprayitno (Iuris Studia: Jurnal Kajian Hukum, 2020)
The legal analysis of the cooperative establishment where the founders are represented by a power of attorney without an intermediary of a legal official is stated in Law No. 25 of 1992 concerning cooperatives.There is no single paragraph that requires that a Statute of a cooperative must be authentic, meaning that the establishment of a cooperative is only required in a written form (deed), that is, it can be a deed without intermediary legal officials and can also be an authentic deed.This is regulated in paragraph (1) of Article 7 of the Cooperative Law.Provisions regarding the establishment and amendment of the articles of association stipulated in the Cooperative Law provide freedom to those who will establish cooperatives to choose whether to use deeds without the intermediary of a legal official or authentic deed